Cement & concrete composites. (Barking, Essex Elsevier, 1990)
"This journal is designed to reflect current developments and advances being made in the general field of cement-concrete composites technology and in the production, use, and performance of cement-based construction materials in general. The word cement is interpreted here in a wide sense to include not only Portland cement but also other matrices such as composite cements, resins, polymers and sulphur. The journal will therefore cover a wide range of composite materials such as fibre cement/concrete composites, polymer cement composites, polymer impregnated composites ferrocement resin concretes, lightweight, wood composites, use of waste material, composite cements, adhesion bonding and fibre reinforced plastics as applied to construction, and material and structural composite systems."
Keywords: Composite-reinforced concrete -- Periodicals; Cement composites -- Periodicals; Concrete -- Periodicals